Ensemble spectral variability study of Active Galactic Nuclei from the XMM-Newton serendipitous source catalogue. (February 2016) - Serafinelli, R; Vagnetti, F; Middei, R
Abstract: The variability of the X-Ray spectra of active galactic nuclei (AGN) usually includes a change of the spectral slope. This has been investigated for a small sample of local AGNs by Sobolewska and Papadakis [1], who found that slope variations are well correlated with flux variations, and that the spectra are typically steeper in the bright phase ( softer when brighter behaviour). Not much information is available for the spectral variability of high-luminosity AGNs and quasars. In order to investigate this phenomenon, we use data from the XMM-Newton Serendipitous Source Catalogue, Data Release 5, which contains X- Ray observations for a large number of active galactic nuclei in a wide luminosity and redshift range, for several different epochs. This allows to perform an ensemble analysis of the spectral variability for a large sample of quasars. We quantify the spectral variability through the spectral variability parameter β, defined by Trevese and Vagnetti [2] as the ratio between the change in spectral slope and the corresponding logarithmic flux variation. We find that the spectral variability of quasars has a softer when brighter behaviour, similarly to local AGNs.